Genistein Increase Intracellular Distribution of the High Motility Group Box-1 through p38 Pathway in HeLa culture cells induced by Tumor Necrosis Factor-Î± - Merlita Herbani; Aris Widodo; Hidayat Suyuti (Journal of Tropical Life Science, 2014)
Cervical cancer is one kind of many cancer that cause death to women around the world. Many studies had support the statement that inflammation has a strong linkage with cancer development. Several factors like proinflammatory factor can influence tumor cell microenvironment, and induce a faster proliferation. TNF-α is suspected can induce proliferation. While cancer itself can induce inflammation, which is marked by several marker. One of them is HMGB1, released from the cell as active secretory lysosomes or passive diffusion. Genistein has demonstrated growth inhibitory effects of various types of cancer cells. It inhibits tyrosine kinase pathway, which can be activated by TNF-α. One of those pathways that have the link with proliferation is p38. This study tries to reveal about inhibitory effect of genistein toward p38 pathway that had been activated by TNF-α. This research was conducted by exposing cultured HeLa cells with various doses of genistein for 90 minutes, and then exposed to TNF - α 10 ng / mL for 20 minutes. Observations were made with a confocal microscope, by staining the cells with pp38-TRITC and HMGB1 antibody. The intensity was measured and analyzed by Fluoview software. The results suggest that there be significant differences between pp38 intranuclear intensity and HMGB1 extranuclear intensity of each dose of genistein (p = 0.000, ANOVA). pp38 and HMGB1 intensity were increased along with increasing genistein dose, but at high dose there were noted decreasing of pp38 and HMGB1 intensity. At apoptotic dose, pp38 and HMGB1 intensity were increased markedly, showing the effect of apoptosis. In general, increasing doses of genistein increase intranuclear p38 activation and HMGB1 extranuclear translocation. So there were a strong linkage between p38 activation and HMGB1 translocation in this study.